Safety and Efficacy of Ureteroscopic Treatment for Ureteral and Renal Stones in Patients of Cirrhosis with Coagulopathy: A Multicenter Experience - Jiaxing Li; Xin Zhang; Meng-Hua Wu; Hui Liu; Xin Zheng (European Urology Open Science)
Background and objective: Upper urinary tract stone treatment in cirrhotic patients with coagulopathy is often delayed due to concerns about bleeding and excessive perioperative management. This study aimed to evaluate the safety and efficacy of ureteroscopy (URS) with holmium:yttrium aluminum garnet (Ho:YAG) laser lithotripsy in such patients through a retrospective case-control analysis. Methods: A total of 170 patients who underwent URS lithotripsy with Ho:YAG laser at Beijing Chao-yang Hospital and Beijing You-An Hospital were analyzed between December 2021 and October 2023. The study included 85 cirrhotic patients with coagulopathy and 85 patients with normal coagulation function as controls. Perioperative data, including blood counts, coagulation profiles, surgical time, hospital stay, immediate stone clearance rates, and complications, were compared between the groups. Key findings and limitations: All procedures were completed successfully. In the cirrhosis group, hemoglobin, platelet count, and thrombin time remained stable, while postoperative activated partial thromboplastin time, prothrombin time, and international normalized ratio increased without causing coagulation-related complications. Immediate stone clearance rates were 96.5% in the cirrhosis group and 95.3% in controls. Although surgical and hospital durations were slightly longer in the cirrhosis group, no significant differences in complication rates or clearance outcomes were observed. Further studies with larger samples are needed to confirm these findings. Conclusions and clinical implications: URS lithotripsy with Ho:YAG laser is safe and effective for cirrhotic patients with coagulopathy when performed with gentle techniques, controlled operative time, and low-pressure irrigation. Abnormal coagulation parameters should not be considered a contraindication for this surgery, and normalization of hemostasis before the procedure is unnecessary. Patient summary: In this study, we confirmed the safety and efficacy of laser lithotripsy in patients with cirrhosis and coagulopathy. We believe that coagulopathy associated with cirrhosis should not be considered a contraindication for laser lithotripsy.